Fashion Collection Design Guidelines for Elderly Women in Bangkok Based on Thai Cultural Heritage - Ponglawhapun, Atthaphon; Utiswannakul, Patcha (Journal of Urban Culture Research, 2022)
Aging populations are increasing significantly worldwide, thereby generating aging societies. Certain product categories that interest elderly women in Bangkok include healthcare, lifestyle fashion, and culture. Cultural heritage are recognized as an important tool that can promote products and brand image. Fashion collection design based on cultural heritage concepts or storytelling have more opportunities to succeed in the fashion market. This research investigates two main points: (1) elderly women’s needs and preferences for fashion products and (2) conceptual guidelines for designing a fashion collection based on Thai cultural heritage. The sample population of this study included 439 elderly women from Bangkok. Our findings proposed conceptual guidelines, with three possible approaches to designing a fashion collection for older women: modern-minimal, luxury-feminine and Boho-ethnic styles. This study includes an implementation of the guidelines with eight prototype outfits.